(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to investigate the effect of amniotic membrane wrapped onto the anastomosis line following colon resection and primary anastomosis on anastomosis healing in rats undergoing pelvic radiotherapy.Material and Methods: Fifty-six male Wistar albino rats were randomly allocated to four main groups. Group I, left colon resection and primary anastomosis; Group II, post-anastomotic amniotic membrane; Group III, preoperative radiotherapy; Group IV, preoperative radiotherapy and amniotic membrane. Radiotherapy was administered under general anesthesia eight and four days prior to surgery at a total of 20 Gy. In the first operation, all the rats underwent 1 cm left colon resection and primary anastomosis. The animals in each group were anesthetized to assess the clinical, mechanical, histologic, and biochemical parameters of anastomotic healing on the third and seventh postoperative days.Results: In the third day groups, anastomosis line bursting was observed in only one subject in those undergoing amniotic membrane wrapping(p0.05) and in all rats in those with no amniotic membrane wrapping. No statistically significant difference was observed in any of the parameters on the histopathological examination of the day 3 groups. The amounts of granulation tissue and fibroblast were significantly higher in the post-anastomotic amniotic membrane group (p0.05), and the macrophage amount was seen to be significantly low in both amniotic membrane groups (p0.05). Conclusion: Amniotic membrane application on the anastomoses in the intestines, either with or without radiotherapy, may contribute to wound healing by positively affecting the anastomosis health.